Environmental politics and policy - Rosenbaum, Walter A. (CQ Press, an imprint of SAGE Publications, Inc., 2023)
"Walter A. Rosenbaum's classic Environmental Politics and Policy provides definitive coverage of environmental politics and policy, lively case material, and a balanced assessment of current environmental issues. The first half of the book sets needed context and describes the policy process while the second half covers specific environmental issues such as air and water; toxic and hazardous substances; energy; and a global policymaking chapter focused on climate change and trans-boundary politics. The twelfth edition includes updates on the Trump administration's initiatives and controversies with regard to environmental policy, offering the currency and relevancy needed for any environmental politics course"--Provided by publisher.